Impact of Financial Market uncertainty and Financial Crises on Dynamic Stock—Foreign Exchange Market Correlations: A New Perspective - Farid Irani; Abobaker Al.Al. Hadood; Korhan K. Gökmenoğlu; Seyed Alireza Athari (SAGE Open)
This study explores how uncertainties in domestic financial markets, including stocks, bonds, and exchange rates, as well as global crises like the subprime mortgage and European sovereign debt crises, affect the dynamic correlation between the Australian stock market index (ASX 300) and foreign exchange rates. Using quantile regression estimation and analyzing high-frequency data from 1999 to 2021, we uncover distinct relationships influenced by currency-specific uncertainties. Our findings reveal that Australian stock market concerns impact co-movements with financial instruments, showing different effects on the correlations with the Euro, British Pound, US Dollar, Japanese Yen, and Chinese Yuan. Surprisingly, uncertainties in the Australian bond market have a negative impact on co-movement with the Euro and British Pound but a positive impact with the US Dollar, Japanese Yen, and Chinese Yuan. Additionally, we observe that volatility in the Australian currency’s exchange rate with various currencies positively influences dynamic co-movements. However, the strength of this connection varies based on the volatility of the Australian dollar against the Japanese Yen. Global financial crises, especially the subprime mortgage crisis, significantly impact dynamic co-movements, supporting both Flow and Stock-oriented theories. In summary, our research sheds light on the diverse impacts of domestic financial market uncertainties on co-movement, providing valuable insights for portfolio managers and foreign investors aiming to understand the intricate relationship between the Australian stock market and exchange rates. JEL Classification : C32, F31, G01, G15